The NAG Sensor NagC Regulates LEE Gene Expression and Contributes to Gut Colonization by Escherichia coli O157:H7 - Le Bihan, Guillaume; Sicard, Jean-Félix; Garneau, Philippe; Bernalier-Donadille, Annick; Gobert, Alain P.; Garrivier, Annie; Martin, Christine; Hay, Anthony G.; Beaudry, Francis; Harel, Josée; Jubelin, Grégory (Frontiers in Cellular and Infection Microbiology, 2017)
Enterohemorrhagic Escherichia coli (EHEC) O157:H7 are human pathogens responsible for bloody diarrhea and renal failures. EHEC employ a type 3 secretion system to attach directly to the human colonic epithelium. This structure is encoded by the locus of enterocyte effacement (LEE) whose expression is regulated in response to specific nutrients. In this study, we show that the mucin-derived sugars N-acetylglucosamine (NAG) and N-acetylneuraminic acid (NANA) inhibit EHEC adhesion to epithelial cells through down-regulation of LEE expression. The effect of NAG and NANA is dependent on NagC, a transcriptional repressor of the NAG catabolism in E. coli. We show that NagC is an activator of the LEE1 operon and a critical regulator for the colonization of mice intestine by EHEC. Finally, we demonstrate that NAG and NANA as well as the metabolic activity of Bacteroides thetaiotaomicron affect the in vivo fitness of EHEC in a NagC-dependent manner. This study highlights the role of NagC in coordinating metabolism and LEE expression in EHEC and in promoting EHEC colonization in vivo.